2015
DOI: 10.1002/ajmg.b.32305
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and dimensional behavioral trait profiles in Costa Rican ADHD sib pairs: Potential intermediate phenotypes for genetic studies

Abstract: Introduction Attention deficit hyperactivity disorder (ADHD) is associated with substantial functional impairment in children and in adults. Many individuals with ADHD have clear neurocognitive deficits, including problems with visual attention, processing speed, and set shifting. ADHD is etiologically complex, and although genetic factors play a role in its development, much of the genetic contribution to ADHD remains unidentified. Methods We conducted clinical and neuropsychological assessments of 294 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 71 publications
3
5
0
Order By: Relevance
“…First, there is strong evidence supporting significant phenotypic differences between ADHD-affected and unaffected individuals in the cognitive domains of mental control (total score and numbers from 20 to 1 of the Mental Control Test), visuomotor skills (copy type and scores of copy and evocation in ROCFT), visuoverbal memory (number of trials in the visuoverbal memory test), phonological and semantic verbal fluency (total score of the verbal fluency test), as well as in language comprehension (Token Test total score), abstraction and problem solving (number of correct responses, total errors, and conceptual-level responses in the WCST), comprehension and verbal reasoning (analogies, vocabulary, digits span, and arithmetic, and comprehension subtests of the WISC-III/WAIS-III), and execution and perceptive reasoning (figure completion, block design, symbol search, and objects assembly subtests of the WISC-III/WAIS-III) (Table 2 and Figure 1a). These results are not only consistent with other studies evaluating potential ADHD cognitive endophenotypes (Peskin et al, 2015; Pineda et al, 2011) but also show how heterogeneous the ADHD phenotype is. In the mid- to long term, these phenotypic differences might allow researchers to dissect the spectrum of cognitive and behavioral phenotypes in ADHD (Cervantes-Henríquez, Acosta-López, Aguirre-Acevedo, Pineda-Álvarez, & Puentes Rozo, 2008; Puentes Rozo, 2009; Puentes-Rozo, Barcelo-Martinez, & Pineda, 2008) and contribute to the better understanding of the etiology, subtypes, and severity of this neuropsychiatric condition (Sonuga-Barke, Dalen, Daley, & Remington, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…First, there is strong evidence supporting significant phenotypic differences between ADHD-affected and unaffected individuals in the cognitive domains of mental control (total score and numbers from 20 to 1 of the Mental Control Test), visuomotor skills (copy type and scores of copy and evocation in ROCFT), visuoverbal memory (number of trials in the visuoverbal memory test), phonological and semantic verbal fluency (total score of the verbal fluency test), as well as in language comprehension (Token Test total score), abstraction and problem solving (number of correct responses, total errors, and conceptual-level responses in the WCST), comprehension and verbal reasoning (analogies, vocabulary, digits span, and arithmetic, and comprehension subtests of the WISC-III/WAIS-III), and execution and perceptive reasoning (figure completion, block design, symbol search, and objects assembly subtests of the WISC-III/WAIS-III) (Table 2 and Figure 1a). These results are not only consistent with other studies evaluating potential ADHD cognitive endophenotypes (Peskin et al, 2015; Pineda et al, 2011) but also show how heterogeneous the ADHD phenotype is. In the mid- to long term, these phenotypic differences might allow researchers to dissect the spectrum of cognitive and behavioral phenotypes in ADHD (Cervantes-Henríquez, Acosta-López, Aguirre-Acevedo, Pineda-Álvarez, & Puentes Rozo, 2008; Puentes Rozo, 2009; Puentes-Rozo, Barcelo-Martinez, & Pineda, 2008) and contribute to the better understanding of the etiology, subtypes, and severity of this neuropsychiatric condition (Sonuga-Barke, Dalen, Daley, & Remington, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Several ADHD studies have identified potential cognitive endophenotypes in neuropsychological tasks such as continuous vigilance, inhibitory control, alteration of temporal perception, delay aversion, working memory alterations, interval timing deficits, fluid intelligence to sustained attention, and visual-motor skills (Acosta-López et al, 2010; Castellanos & Tannock, 2002; Henriquez-Henriquez et al, 2014; Hwang-Gu & Gau, 2015; Mastronardi et al, 2016; Pironti et al, 2014). Recently, we and others have identified ADHD endophenotypes in families ascertained from two well-characterized genetic isolates, the Paisa community in Antioquia, Colombia (Mastronardi et al, 2016; Pineda et al, 2011) and the Central Valley in Costa Rica (Arcos-Burgos & Muenke, 2002; Peskin et al, 2015). In these studies, several measures of cognitive intelligence, attention, visual and motor skills, verbal coefficient, sustained visual attention, and visuospatial problem resolution reported high heritability values and strong association to the ADHD status (Peskin et al, 2015; Pineda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heritability of personality dimensions in the total 543 family members was estimated using Sequential Oligogenic Linkage Analysis Routines (SOLAR) . SOLAR is an extensive, flexible software package for genetic variance components analysis, including linkage analysis, quantitative genetic analysis, single‐nucleotide polymorphisms (SNP) association analysis (QTN, QTLD, and MGA), and covariate screening.…”
Section: Methodsmentioning
confidence: 99%
“…An endophenotype is a heritable, measurable trait or feature that is associated with a disorder of interest, but is state independent (e.g., manifests in individuals whether or not they are manifesting the disorder, including in unaffected family members). No endophenotypes have yet been identified for TS, but specific neurocognitive abnormalities have been suggested as potential endophenotypes for two related disorders that are highly comorbid with TS, obsessive compulsive disorder (OCD; Pauls et al, 2014a ), and attention deficit hyperactivity disorder (ADHD; Pineda et al, 2011 ; Eddy and Cavanna, 2014 ; Peskin et al, 2015 ). The study by Beth Hobson (University of Birmingham), and her colleagues, takes the first step in identifying potential TS endophenotypes by investigating whether neurocognitive dysfunction is consistently associated with TS.…”
Section: Introductionmentioning
confidence: 99%